PROGRESUL INDIVIDUAL SUB SEMNUL EGALITĂŢII CU PROGRESUL INSTITUTIONAL - BUTUCEL, Elena; KULIKOVSKI, Lidia (BIBLIOPOLIS, 2020)
The study realized by the Department of Librarianship and Information Assistance “The efficiency of the workplace at the Municipal Library B.P. Hasdeu” oriented to identifying problems, searching solutions, highlighting the workplace efficiency and forecasting this management type in the practice of library science has emphasized some aspects. The article presents only 5 questions related to the professional development and the personal career. The results reveal that the abilities’ development is closely related to the support of manager, colleagues, and team. The study underlines the follow aspect – emotional ties between the colleagues. These relations, the need to be accepted personally and occupationally are very important. As a generalizing element, the research results help to anticipate, to realize and manage situations in order to improve them. They relate to communication, relation manager - employee, employee - employee, employee at center - employee at the periphery, employee in vital structure – employee in a routines’ structure etc. If you have not excellent employees you have not excellence in the activity